2011
DOI: 10.3390/mi2030345
|View full text |Cite
|
Sign up to set email alerts
|

An Electromagnetically-Actuated All-PDMS Valveless Micropump for Drug Delivery

Abstract: This paper presents the fabrication process of a single-chamber planar valveless micropump driven by an external electromagnetic actuator. This micropump features a pair of micro diffuser and nozzle elements used to rectify the fluid flow, and an elastic magnetic membrane used to regulate the pressure in the enclosed fluid chamber. Polydimethylsiloxane (PDMS) is used as the main construction material of this proposed micropump, including the structural substrate and the planar actuation membrane embedded with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…Guo et al [15] reported a parallel double chamber as a modification to the basic valveless micropump design. Zhou et al [16] reported a PDMS based electromagnetically actuated micropump. Yamahata et al [17] proposed an electromagnetically actuated valveless micropump with PMMA and PDMS as substrate materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al [15] reported a parallel double chamber as a modification to the basic valveless micropump design. Zhou et al [16] reported a PDMS based electromagnetically actuated micropump. Yamahata et al [17] proposed an electromagnetically actuated valveless micropump with PMMA and PDMS as substrate materials.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review, it is clear that experimental investigations of PZT actuated valveless micropumps including microfabrication and experiments have been reported by various research groups in the past few years [11][12][13][14][15][16][17][18][19][20][21]. Also, many approximate analytical and simulation models have been reported [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Transdermal and subcutaneous drug delivery systems using micro needle [6][7][8], for instance, have been proven as a viable method in delivering adequate dosage administration across the skin. Nonetheless, most of the micropumps proposed [9][10][11] for drug delivery application involve utilizing active power circuitry, making the system tend to have relatively large dimensions with limited space and constricted the system's mobility. These difficulties will be increased when multiple drug delivery components are required and making power management a key design feature.…”
Section: Introductionmentioning
confidence: 99%
“…The micropump can generate maximum flow rate of 41μLmin −1 at 25kPa backpressure [1]. Zhou et al, studied the fabrication and process of valve less, single-chamber planar PDMS micropump driven by an external magnetic actuator [6]. Maximum flow rate of 319.6μLmin −1 and a maximum hydrostatic backpressure of 950 Pa (9.5 cm H2O) were exerted by the micropump.…”
Section: Introductionmentioning
confidence: 99%